Fuzzy-based Decision for Coronary Heart Disease Diagnosis: Systematic Literature Review - Afrina Safira Dianirani; Zefanya Debby Claudia (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
Coronary heart disease is usually caused by a buildup of fatty material and plaque inside the coronary arteries. The death rate caused by coronary heart diseases is threatening around the world. For the past two decades, most of the people from developing countries are suffering from heart disease. Diagnosing these diseases at earlier stages helps patients reduce the risk of death and also in reducing the cost of treatment. Decisions in medical diagnosis are mostly taken by expert’s experiences. In many cases, not all the expert’s experiences contribute towards effective diagnosis of a disease. Many alternative methods have been suggested for medical diagnosis in the healthcare domain. However, evaluating the functionality of coronary heart diseases diagnosis systems remains challenging. The purpose of this paper is to perform a study on literature related to fuzzy-based decision for diagnosis of coronary heart disease. Accordingly, the research gathered studies related to fuzzy-based decision for diagnosis of coronary heart disease between the periode 2016-2021.